Curriculum Innovation in Arabic and Islamic Studies through Entrepreneurial Approaches in Nigerian Universities - Yahya Isiaq Oluwatosin; Olaniyan-Shobowale Khadijat Olushola; Owoyale-Abdulganiy Ibrahim Solahudeen; Zakariyah Mikhail Poopo; Kewulere Adam Olasunkanmi (Yayasan Letiges Konsultan Sosial, 2026)
This research investigates entrepreneurial strategies for curriculum development and enhancement in Arabic and Islamic studies education in Nigeria to meet the demands of the 21st century. Nigeria, with its rich Islamic heritage and rapidly evolving educational landscape, presents a unique context for exploring innovative approaches to curriculum design. The study focuses on integrating entrepreneurial principles, skills, and pedagogies into the Arabic and Islamic studies curriculum to equip students with the competencies needed for success in the modern world. Drawing on qualitative and quantitative research methods, the research examines current curriculum frameworks, pedagogical practices, and educational policies related to Arabic and Islamic studies in Nigeria. It explores the feasibility, effectiveness, and challenges of incorporating entrepreneurial concepts such as critical thinking, problem-solving, and innovation into the curriculum. Additionally, the study investigates the role of community engagement and stakeholder collaboration in enriching the curriculum with real-world learning experiences. Through this research, insights were gained into how entrepreneurial strategies can enhance Arabic and Islamic studies education in Nigeria, empowering students with the skills, knowledge, and mindset necessary to thrive in the dynamic global landscape of the 21st century.